PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA TEGAL WARU, KECAMATAN CIAMPEA, KABUPATEN BOGOR - Thantawi, Tubagus Rifqy; Purwati, Dewi; Amalia (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2025)
This service aims to help Tegal Waru village community, Ciampea District, Bogor Regency. In implementing family financial planning with sharia principles. Many families in this village face financial financial problems, such as limited income, consumptive spending, and no emergency fund. emergency fund. To overcome these problems, the community service activities are carried out using the Participatory Action Research (PAR) method, method, which involves active community participation, namely socialization, training, and mentoring. mentoring. This program teaches the basics of sharia finance, how to manage family finances according to Islamic teachings, and how to make an appropriate budget. budget. With this training, it is hoped that families in Tegal Waru village will be able to make their own financial planning. in Tegal Waru village can make a better financial plan, which can help them manage their expenses, prepare an emergency fund, and make a budget. can help them manage their expenses, set up an emergency fund, and plan for a more stable financial future. plan for a more stable financial future